Women on Screen: K-dramas and Gender Rewritings (2015-2025): From Webtoon to Television; Female Authorship, Graphic Adaptation, and Transnational Reception - Roca Vera, Dácil; Díaz Mesa, Haridian; Morales Domínguez, Lucas (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This article examines how South Korean television adapts webtoons created by women within historically male-dominated film and comics industries. It positions K-dramas as the site where cultural adaptation is negotiated and their transnational impact on audiovisual representation is amplified. Drawing on a corpus of twenty-three adaptations, it combines close textual reading, thematic analysis and audience indicators to observe how industrial and authorial decisions amplify or attenuate the feminist impulses of the graphic source material. Findings show that series tend to romanticise structural conflicts and stylise bodies according to dominant beauty canons, yet they also consolidate forms of female agency, displace hegemonic stereotypes and introduce affective masculinities. Salient themes include gendered relational dynamics and social pressures, alongside empowerment, role challenge and workplace equality; mental health and harassment emerge, but less frequently. Where women participate substantively in adaptation (writing or direction), the television version more clearly preserves the original’s critical tone.